Techno-economic optimal planning of an industrial microgrid considering integrated energy resources - Ahmed, Mohammad Adel; Abbas, Ghulam; Jumani, Touqeer Ahmed; Rashid, Nasr; Bhutto, Aqeel Ahmed; Eldin, Sayed M. (Frontiers in Energy Research, 2023)
Microgrids have benefited energy systems by getting rid of the abundant use of traditional energy resources, replacing them with distributed generations (DGs). The use of DGs in microgrids not only provides clean and green energy but also reduces the gigantic losses in transmission and distribution lines. Widespread adoption of renewable energy in microgrids saves customers from high fuel prices and provides a sustainable replacement for future fossil fuel depletion. Microgrids have proven to be the latest and most advanced power systems due to their new capabilities to operate in both grid-connected and isolated modes. Microgrids use multiple energy sources simultaneously, which can offset the intermittent behavior of renewable energy sources. In this study, we planned and optimized an industrial microgrid with an annual increase in load, which contains dispatchable generation, non-dispatched generation, and energy storage. In addition, to test the different behavior of a microgrid operating independently or in grid-tied mode, four typical days were selected to show the load demand and solar and wind energy forecast data for the entire year. The power output curves for each typical day were analyzed for every year in both stand-alone and grid-connected modes. Furthermore, to validate the feasibility of the microgrid, the investment and operations costs were also calculated in the paper.